2013
DOI: 10.1590/s1516-89132013000500020
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of coastal water quality in bay of Bengal and Palk Strait, Tamilnadu, Southeast Coast of India

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The study area observed the nitrate content varied from 1.84μg/L to 4.85 μg/L, highest values recorded during monsoon and immediate post-monsoon seasons, due to the influx of river and land runoff and decomposition of mangrove leaf litterfall in the adjacent mangrove environments by the seasonal influence. Srinivasan et al, (2013) observed nitrate levels ranging from 0.17 to 6 μmol/L in the coastal waters of the Bay of Bengal and Palk Strait. Kalaiarasi et al, (2012) found the nitrate values from 2.125 to 5.820 μg/L in S. P. Pattinam and 1.473 to 4.010 μg/L in Manamelkudi of Palk-Strait (Fig.…”
Section: Nitratesmentioning
confidence: 94%
See 1 more Smart Citation
“…The study area observed the nitrate content varied from 1.84μg/L to 4.85 μg/L, highest values recorded during monsoon and immediate post-monsoon seasons, due to the influx of river and land runoff and decomposition of mangrove leaf litterfall in the adjacent mangrove environments by the seasonal influence. Srinivasan et al, (2013) observed nitrate levels ranging from 0.17 to 6 μmol/L in the coastal waters of the Bay of Bengal and Palk Strait. Kalaiarasi et al, (2012) found the nitrate values from 2.125 to 5.820 μg/L in S. P. Pattinam and 1.473 to 4.010 μg/L in Manamelkudi of Palk-Strait (Fig.…”
Section: Nitratesmentioning
confidence: 94%
“…Srilatha et al, (2013) reported DO from 3.92 to 5.22 mg/L and 3.97 to 5.33 mg/L at Point Calimere, and Muthupettai mangroves respectively. Srinivasan et al, (2013) reported DO in the range of 5.5 to 6.4 mg/L while working on Vedaranyam mangroves (Fig. 8).…”
Section: Dissolved Oxygen (Do)mentioning
confidence: 99%
“…The concentration of nitrate and phosphate ions in the estuaries, rivers, and pond water was found in a lower extent. Srinivasan et al (2013) studied the coastal rivers of the southeast coast of India and showed that the variations of the nitrate values ranged from 0.17 to 6 μmol/L. However, the nitrite concentration fluctuated between 0.02 and 0.55 μmol/L.…”
Section: Characterization Of Physicochemical Parametersmentioning
confidence: 99%
“…Coastal water is defined as a zone where land and water interact with each other (Moksness et al, 2013), serves as an important settlement area for human and home for various species of fishes, molluscs, prawns and crabs, providing natural foods for human as well as daily income for the locals (Srinivasan et al, 2013;Obatitor, 2014). Miri is a coastal city, located in the northwest part of Sarawak, Malaysia, which has an open coastline type facing the South China Sea, ranging from the mouth of Baram River until Tanjong Lobang beach (Ee & Zae, 2010).…”
Section: Introductionmentioning
confidence: 99%